The Effect of the Problem-Based Learning (PBL) Model in the Context of Socio-Scientific Issues (SSI) on Critical Thinking Ability on Digestive System Material - Aisy, Maitsaa Rihhadatul; Trisnowati, Eli; Siswanto, Siswanto (Jurnal Inovasi Pendidikan IPA, 2024)
Science education emphasizes direct experience to develop competence in exploring and understanding nature to foster the ability to think critically, collaborate, be scientific, and communicate as important aspects of life skills. This research aims to analyze the effect of learning using the problem-based learning (PBL) model in the context of socio-scientific issues (SSI) on critical thinking skills on digestive system material. This research is quantitative research using a quasi-experimental design. The population is class VIII students of State Junior High School 2 Subah for the 2023/2024 academic year. The sample was class VIIIA as the experimental class and class VIIIC as the control class, established using the purposive sampling technique, namely sampling based on certain considerations.  The research instrument was a test (pretest and posttest). The research results are as follows. (1) The results of the T-test analysis using the Independent Sample t-test are 0.00 < 0.05, which shows that there is a difference in the average value of critical thinking abilities of the two classes. (2) The results of the N-Gain test for the experimental class obtained a higher value, namely 0.628, indicating that the experimental class using the PBL model with the SSI context experienced a greater increase in critical thinking abilities. (3) The effect size test result is 1.1659 in the high category. This research concludes that the PBL model in the context of socio-scientific issues (SSI) affects critical problem-based learning thinking skills.